Improved team communication in endoscopic procedures by digital enhanced telecommunication during the COVID-19 pandemic - Sturm, Niklas; Perkhofer, Lukas; Schulte, Lucas; Mayer, Benjamin; Seufferlein, Thomas; Wagner, Martin; Walter, Benjamin M. (Endoscopy International Open, 2022)
Background and study aims Unbiased communication is crucial for excellent teamwork in high-quality endoscopy. Personal protective equipment (PPE) (FFP-masks and face-shields) worn by endoscopists that are ubiquitous in the current COVID-19 pandemic strikingly impair communication. Digital enhancement approaches to maintain team communication, especially during complex endoscopic procedures, are urgently warranted.Materials and methods A prospective, two-armed interventional study was performed at an endoscopy unit at a tertiary center in Germany. Two hundred and three endoscopic procedures with PPE se according to pandemic risk level were randomly assigned (1:1) to a group performed by an endoscopy team equipped with digital enhanced cordless telecommunication (DECT) or one without digital-enhanced communication. The primary outcome was the team-reported number of communication-associated events (CAEs) defined as misunderstandings that impaired workflow during endoscopic examination. Secondary outcomes included perceived voice and headphone quality and overall comfort with DECT during endoscopic work.Results The use of DECT was associated with a significant reduction in communication-associated events in endoscopic procedures and overall, was perceived positively.Conclusions Digital enhancement of communication is a promising and easy-to- establish tool for improving team communication quality in endoscopy.